(untitled) (Research, Society and Development, 2022)
This research presents itself as a bibliographic review study with the main objective of understanding the main congenital heart diseases in patients with Down Syndrome and pointing out new updates on the subject. Down Syndrome (DS) is a genetic condition that can lead to severe physical and cognitive disabilities. Currently, most people with the disease do not have major difficulties in daily life and lead a relatively normal life as a result of the advancement and support of medicine. However, there are diseases that are more prevalent in DS when compared to the general population. With this, it is of great importance to point out what these diseases are and how they interfere in daily life so that these patients are provided with better living and health conditions. Congenital heart disease is the most prevalent comorbidity associated with Down Syndrome, with atrioventricular septal defect (AVSD) being the most common malformation. This alteration is caused as a result of the impediment of fusion of the embryonic endocardial cushions. Other malformations found in less prevalence are atrial septal defect (ASD), ventricular septal defect (IVC) and Tetralogy of Fallot. In-hospital mortality was significantly lower in populations undergoing cardiac intervention in heart diseases with lower proportions of cardiac arrest and less need for ECMO during hospitalization. The prevalence of heart disease in patients with Down Syndrome is notorious, however, further research is crucial to better understand its etiology.